Health spending efficiency in developing Asia - Donna Faye Bajaro; Yothin Jinjarak; Yuho Myoda; Donghyun Park; Pilipinas Quising (Asian Development Bank (ADB), 2023)
The coronavirus disease (COVID-19) pandemic placed health-care systems around the world under great stress. The sharp increase in demand for health care highlighted the importance of efficient health spending. The negative impact of the pandemic on global economic growth further strengthened the case for efficient health spending. In this paper, we examine health spending efficiency in developing Asia. Using data envelopment analysis, we find that East Asia has the highest average output- and input-oriented technical efficiency scores among the subregions. Universal health coverage service coverage index and population density have the strongest effect on health spending efficiency. In addition, using the novel framework of macro-level efficiency analysis, we find that developing Asia falls short of optimal total health expenditures. Caucasus and Central Asia has the highest average allocative efficiency score among the subregions. Overall, developing Asia has substantial room for improvement in both technical and allocative efficiency.
Keywords: C10; C60; H51; I10; 330; health spending; data envelopment analysis; technical efficiency; allocative efficiency